A internacionalização como critério de avaliação na sociedade da auditoria: uma análise comparativa entre os programas de direito e educação - Barbosa, Wlly Annie Feitosa (2021)
In today's world of accountability, valuation for the evaluation and ranking of institutions and courses, we can say that we live in the audit society, including with regard to Higher Education, which, with the dissemination of technologies and innovations that permeate the scenario academic demands about productivity, has been influencing the Brazilian Graduate Studies, especially the Graduate System and the evaluation criteria and mechanisms that have been used by the Coordination for the Improvement of Higher Education Personnel (CAPES), responsible for promoting the courses and their evaluation in Brazil. This dissertation work aims to get to know the postgraduate assessment system in Brazil and the changes recently made in its criteria, with a more restricted look at the Internationalization indicator, since it configures an express concern of CAPES and PNPG (2011-2020), and the differences and similarities found in the evaluation sheets in the areas of Law and Education, two major areas of the College of Humanities. Through the analysis of the reports and evaluation sheets of these two Areas, in relation to the internationalization item. To achieve this general objective, we address as specific objectives the discussion about the evolution of Brazilian Postgraduate Studies, the analysis of the postgraduate policy proposed by CAPES, expressed in the National Postgraduate Plan 2011- 2020 and the documents in the area of Law and Education in the last evaluations, as well as the analysis of the evaluation sheets applied to these two areas, in light of the Internationalization indicator. Therefore, we used the hypothetical-deductive method, in a bibliographical and documentary research with a qualitative approach, considering that the work was organized in order to verify the applicability of the evaluation policy currently used by CAPES and the inferences to be proposed by this work . Finally, we verified the attribution of different weights and mechanisms for the implementation and evaluation of internationalization, due to the cultural and social capital of each area, in terms of Pierre Bourdieu's Theory of Sociology of Education.